Influence of Flooding on the Survival of Arbuscular Mycorrhiza (Bangladesh Journal of Microbiology, 2010)
A study was conducted for two consecutive years (2004-2005 and 2005-2006) at Ullapara, Shirajgonj particularly in onion growing flooded area to know the status of arbuscular mycorrhizal fungi (AM) in flooded soil. Twenty farmers were selected for two years who cultivated onion in their fields after flood. Soil samples were collected just after removing of flood water. Again rhizosphere soils with roots of onion were collected from the same plots. After assessment of these samples, two years' results indicate that there is a plenty of AM spores in flooded soil. It proves their ability to survive in flooded condition and after flooding heavy colonization in onion roots was observed. Higher spore population was also recorded from the rhizosphere soils of onion. Keywords: Arbuscular mycorrhiza; flooding; survivabilityDOI: http://dx.doi.org/10.3329/bjm.v25i2.4872 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 111-114